PERANAN JUST IN TIME METHOD UNTUK PENINGKATAN PRODUKSI PERUSAHAAN - Willem Willem (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2018)
Market competition that is not only in national scope, transportation and communication tool progress have encouraged global competition. Technology advance plays an importance role in short goods circulation and increasing various types of produced goods. This research aims to determine (1). Any non value Added activities leading to non value added costs in the company (2). The extent of benefits and roles of Just In Time (JIT) Method in eliminating all non value activities or sources (3). To provide description on the importance of Just In Time application for the company in order to improve efficiency and productivity. This research used descriptive method, namely the research giving description on certain activity or project systematically, factually and appropriately and there are also some necessary analyses to overcome any faced problems and to find out any alternatives that can be used to anticipate various developments to be adjusted with the theory. Results of the research conclude that (1). Success in reducing or making efficient production cost can be seen in sale by savings (2). The figure is obtained from comparison of cost of goods before the JIT production system implementation with the cost of goods after the JIT production system implementation. (3) by reducing cost of goods, it is expected that the company can reduce its cost of sale, with the aim to add product competitiveness in the market and the company will obtain increased level of profits. (4) it can be seen that before the implementation of JIT production system, the company profit has increased after the implementation of JIT production system. Keywords: Just In Time Method, Company Production Increase